Efeitos da densidade de plantio sobre a cultura do feijoeiro - Vieira, Clibas (Revista Ceres, 2025)
In Vigosa, State of Minas Gerais, eight spacings of field bean (Phaseolus vulgaris L.) were compared. The combinations of spacing were made up of two different row spacings (40 and 50 cm.), with four different intervals between seeds in the row (2.5, 5, 7.5, and 10cm). The variety ’Rico-23’ was used and the experiment was conducted five times: three in the nwetn period and two in the «dryw period.